PENERAPAN PEMBELAJARAN KONTEKSTUAL DENGAN MODEL PROBLEM BASED LEARNING - Titis Puspitaningrum Dewi Kartika (JURNAL PENDIDIKAN AKUNTANSI (JPA), 2012)
Abstract: This study aims to determine the application of contextual learning with PBL model to improve the ability of questioning and answering. This is an action research class (PTK) that was designed in two cycles. The first cycle was to carry on the topic of profit and loss statement, while the second cycle was on the rest of financial statement. The subjects of this study were accounting students at SMK Salahudin Malang. Data analysis was performed using the percentage increase of studentsâ ability to questioning and answering of each cycle. The results show that the implementation of contextual learning with PBL model can improve the ability to questioning and answering. Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â  Keywords: Contextual learning, PBL, questioning and answering, learning outcomes.